To study about the policy response to the cyber-Terrorism: Examining the Government's Response to Cyber-Attacks and Cyber-Terrorism (Journal of Advances and Scholarly Researches in Allied Education, 2021)
When cyber incidents occur, the government assists potentially impacted entities, analyses thepossible impact across key infrastructure, investigates those responsible with law enforcement partners,and coordinates a national response to major cyber catastrophes. To achieve better unity of effort and awhole-of-nation response to cyber events, the Department collaborates closely with other agencies thathave complementary cyber responsibilities, as well as private sector and other non-federal owners andoperators of vital infrastructure. This article examines the government's response to cyber-attacks andcyber-terrorism.